Comparative study on the application of green accounting based on university social responsibility at Universities in Pontianak - Henri Prasetyo; Ika Kurnia Indriani; Agus Widodo (Journal of Islamic Accounting and Finance Research, 2020)
Purpose - The purpose of this research is to know the difference of university social responsibility on green accounting implementation at Tanjungpura University with other universities in Pontianak City.  Green accounting is a style of accounting that describes efforts to incorporate environmental benefits and costs into making economic decisions or business financial results.Method - The objects of this research are audit committee, internal auditors, internal supervisory units and officers, lecturers, or staff at universities in Pontianak City who know about responsibility in managing the environment. This study uses accidental sampling in Tanjungpura University, Pontianak State Polytechnic, Muhammadiyah University of Pontianak, and Panca Bhakti University. The data analysis in this study was done by using Mann Whitney U-test.  Result - The results of this study indicate that there are significant differences between the Tanjungpura University with other universities in Pontianak City on environmental involvement, environmental reporting, and environmental audit; while for environmental concern, there is no difference between the University Tanjungpura with other universities in the Pontianak City.Implication - Universities in Pontianak City are suggested to improve their performance related to the environment, especially in environmental involvement, environmental reporting, and environmental audit.Originality - This research is the first study that used four universities as the research objects.